2012
DOI: 10.1111/j.1528-1167.2011.03380.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy control following intracranial monitoring without resection in young children

Abstract: Summary Purpose:  Intracranial monitoring (IM) is a key diagnostic procedure for select patients with treatment‐resistant epilepsy (TRE). Seizure focus resection may improve seizure control in both lesional and nonlesional TRE. IM itself is not considered to have therapeutic potential. We describe a cohort of patients with improved seizure control following IM without resective surgery. Methods:  Over 12.5 years, 161 children underwent 496 surgeries including intracranial monitoring. We retrospectively reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Our results support the feasibility of epilepsy surgery in children with ASD, highlight the potential for improved seizure control and associated cognitive-behavioral gains, and attest to the safety of surgical intervention in this population. 21,37,38 Contrary to the prevalent concern that epilepsy surgery in patients with ASD may have limited utility, 10,11,14,40,45 we found that even for severely affected individuals, surgery often had tangible benefits, reducing the burden of seizures and aberrant behaviors on the families and facilities that provide lifelong care to these patients, many of whom require special medical attention and very substantial support due to the presence of developmental delay and other comorbidities.…”
Section: Discussionmentioning
confidence: 54%
“…Our results support the feasibility of epilepsy surgery in children with ASD, highlight the potential for improved seizure control and associated cognitive-behavioral gains, and attest to the safety of surgical intervention in this population. 21,37,38 Contrary to the prevalent concern that epilepsy surgery in patients with ASD may have limited utility, 10,11,14,40,45 we found that even for severely affected individuals, surgery often had tangible benefits, reducing the burden of seizures and aberrant behaviors on the families and facilities that provide lifelong care to these patients, many of whom require special medical attention and very substantial support due to the presence of developmental delay and other comorbidities.…”
Section: Discussionmentioning
confidence: 54%
“…1B) and ECoG was recorded by the device. Remarkably, the subject subsequently became seizure-free (now over two years), as can rarely occur after intracranial monitoring (Katariwala et al, 2001; Roth et al, 2012). While the neurostimulator continued to record and store ECoG, the responsive stimulation function of the device was never enabled.…”
Section: Resultsmentioning
confidence: 86%
“…[2][3][4] There was a similar decrease in seizure frequency whether stimulation is on or off and is referred to as the "implantation effect. 7,8 The absence or decrease in frequency of seizures during iEEG monitoring can result in inability to localize seizure origin, and also results in prolonged hospital stays with increased morbidity and healthcare expense. Every major epilepsy center has patients to report with history of frequent seizures that did not have any after iEEG placement despite withdrawal of medications.…”
Section: Introductionmentioning
confidence: 99%
“…Very rare patients with drug-resistant epilepsy that underwent iEEG monitoring became seizure-free without resection of the epileptogenic focus. 7,8 The absence or decrease in frequency of seizures during iEEG monitoring can result in inability to localize seizure origin, and also results in prolonged hospital stays with increased morbidity and healthcare expense.…”
Section: Introductionmentioning
confidence: 99%